2018
DOI: 10.1039/c8ew00313k
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the limits of anaerobic biodegradability of urban wastewater by AnMBR technology

Abstract: Anaerobic membrane bioreactors (AnMBRs) can achieve maximum energy recovery from urban wastewater (UWW) by converting influent COD into methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
3
15
3
Order By: Relevance
“…The average dissolved methane removal efficiency with conditions of 0.55 m 3 m –2 d –1 of normalized flow and 44 mmHg of absolute pressure was 79 ± 2%. Despite being subjected to seasonal variations, the results were similar to those observed in an upflow anaerobic sludge blanket (UASB) reactor study (68 ± 7%) and in a temperature-controlled pilot-scale AnMBR study (67%). ,, In this study, removal efficiencies up to 66% were observed during tests in the summer, whereas removal efficiencies up to 83% were observed in the fall and winter. This difference may have been due to further optimization of the membrane contactor setup rather than an effect of seasonal variations, however.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The average dissolved methane removal efficiency with conditions of 0.55 m 3 m –2 d –1 of normalized flow and 44 mmHg of absolute pressure was 79 ± 2%. Despite being subjected to seasonal variations, the results were similar to those observed in an upflow anaerobic sludge blanket (UASB) reactor study (68 ± 7%) and in a temperature-controlled pilot-scale AnMBR study (67%). ,, In this study, removal efficiencies up to 66% were observed during tests in the summer, whereas removal efficiencies up to 83% were observed in the fall and winter. This difference may have been due to further optimization of the membrane contactor setup rather than an effect of seasonal variations, however.…”
Section: Resultssupporting
confidence: 85%
“…Psychrophilic temperature operation of anaerobic technologies leads to a potentially significant fraction of the total methane remaining dissolved in the membrane permeate. While various factors including temperature, COD, methane supersaturation, and ultrafiltration (UF) membrane operating conditions affect the fraction of total methane that is dissolved, several bench and pilot-scale AnMBRs have reported that greater than 40% of the total methane generated was dissolved in the permeate when operating below 25 °C. Left unaddressed, the dissolved methane runs the risk of escaping to the atmosphere where it may act as a greenhouse gas (GHG) with a global warming potential (GWP) 25 times more potent than CO 2 . , In addition to limiting its impact on the environment, recovering dissolved methane can further drive the system toward energy neutrality. Several dissolved methane recovery technologies have been proposed as possible solutions including biological oxidation and air stripping, but separation by membrane contactor in particular has been noted for its low energy requirements and the potential to recover the methane in a form suitable for use as a fuel. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CH 4 can be recovered (both as biogas and dissolved in effluent) and be used to cover a part of the energy demand of the treatment process, leading to a need to meet little or no energy requirements [172,177]. Seco et al [153] demonstrated that considering the calorific power of methane (38,000 KJ/m 3 ) and the typical efficiency of a combined heat and power device (35%), the specific energy produced by the biogas in the AnMBR pilot plant would be 0.073 kWh/m 3 of treated water. In another study [156], it was found that the energy recovered from both biogas and dissolved CH 4 produced in the AnMBR used for the treatment of municipal wastewater can be up to 0.347-0.389 kWh/m 3 .…”
Section: Energy Demandmentioning
confidence: 99%
“…Another important factor in the development of this technology is the latest stringent regulations imposed for environmental discharge worldwide, the reduction in membrane cost, the continuous improvement in process design, and requirements of high-quality water reuse applications [2]. The anaerobic membrane bioreactor (AnMBR) is a consolidated technology for the wastewater management and treatment [3,4]. Several studies for urban and industrial wastewater treatment have already been carried out, showing significant efficiency improvements compared to conventional activated sludge treatment [5].…”
Section: Introductionmentioning
confidence: 99%